Haemoglobin-E disease in children: global and Bangladesh perspective - an updatB - Rahman, AKMM; Uddin, MK; Hossain, MZ; Ahmad, M; Begum, RS; Ghosh, AK; Fatmi, LE; Das, SR (Journal of Dhaka Medical College, 2012)
DOI: http://dx.doi.org/10.3329/jdmc.v20i2.10549 J. Dhaka Med. Coll. 2011; 20(2): 193-198